Socialization of personality of primary school child in a collective and inthelearning environment - Шимко, І. М. (Pedagogy of Higher and Secondary Education, 2013)
Shimko I. M. Socialization of personality of primary school child in a collective and inthelearning environment. The article realizes with the theoretical analysisof the problem of personality primary school child in acollective, opens with the essence and the peculiar propertiesof the socialization of primary school child in a collective and the learning environment.